Assessing the Viability and Potential for Developing Tourism Industry in Lavasan City using the IUCN Model - Askarpour, Elnaz; Asadian, Farideh; Arzjani, Zahra (International Journal of Bio-resource and Stress Management, 2011)
Rapid urbanization and geographical patterns in recent decades have encouraged tourism as one of the biggest industry and the most important goal for many countries. Due to this reason in recent years, tourism and recreational places have been considered enough importance. In this discussion, the potentiality of Lavasan city has been considered in developing tourism industry. The aim of this investigation includes studying and describing the potential and some eco-tourism options to develop eco-tourism and geo-tourism in Lavasan. GIS and standards of International Union for Conservation of Nature (IUCN) were used for evaluation followed by short analysis.